Pengaruh Penggunaan E-Storybook Dongeng Sastra Berbasis Kearifan Lokal terhadap Karakter Anak di Sekolah Dasar - Fitriana; Indah; Adi Apriadi Adiansha (Jurnal Guru Sekolah Dasar, 2025)
The character crisis in elementary school students is still a fundamental problem in the world of education, characterized by low attitudes of responsibility, honesty, and empathy. This requires learning innovations that are able to instill character values in a contextual and interesting way. This study aims to determine the effect of using local wisdom-based literary fairy tales E-Storybook on the character of grade IV students at SDN Talabiu. The research used quantitative methods with a pseudo-experimental design (one group pretest-posttest). The research subjects amounted to 15 students. The instruments used include observation, questionnaire, and character assessment scale. The results showed that the average character score increased from 61.3 (pretest) to 80.1 (posttest). The paired samples t-test showed a significance value of p < 0.001. This finding confirms that E-Storybook is effective in strengthening students' character through a local culture-based digital literature approach.